Biomimetics through nanoelectronics : development of three dimensional macroporous nanoelectronics for building smart materials, cyborg tissues and injectable biomedical electronics /: development of three dimensional macroporous nanoelectronics for building smart materials, cyborg tissues and injectable biomedical electronics. ([2018]) - Liu, Jia
No abstract available